Fármacos como poluentes emergentes em ambientes aquáticos: panorama de consumo na Região Metropolitana de São Paulo e quadro comparativo de políticas públicas entre países - Aragao, Rafaela Barbosa de Andrade [UNIFESP] (2018)
Water pollution has been an increasingly constant concern to the responsibles for planning and doing public policy actions. In this research, we discuss the emerging pollutants in aquatic environments with a focus on pharmaceuticals. The primary objective is to identify the main commercialized pharmaceuticals in the Metropolitan Region of São Paulo (MRSP) and to compare public policies focused on pharmaceuticals in the environment among several countries. For that, data related to the commercialization of pharmaceuticals in the MRSP between April / 2016 and April / 2017, available from Close-Up International, was compiled and processed. The 300 pharmaceuticals most commercialized in the MRSP were classified in 26 therapeutic classes, which include 159 drugs. The most commercialized pharmaceutical group in the period belong to the therapeutic classes: analgesics, antipyretics, nonsteroidal and antirheumatic anti-inflammatories, representing approximately 48% of the sample. The ten most commercialized active principles sum up 1,200 tons that circulated in the MRSP. Among them, the first is the dipyrone, with 488 tons commercialized. Public policies focused on pharmaceuticals in the environment even in developed countries still needs adjustments to improve efficiency. There is no international standard on how to conduct the issue, each country adopting the public policy that best matches to the local. Brazil, despite having some legislation that approaches the theme, still lacks efficient public policies and stakeholder awareness. In this aspect, the need for improvement of the reverse logistics system, consumer orientation to the adequate disposal of pharmaceuticals, and the adoption of the unit dose as a therapeutic strategy is evident.